Long-term clinical evidence of comparable efficacy and toxicity of nivolumab and pembrolizumab in advanced melanoma treatment. Issue 3 (3rd June 2023) - Cybulska-Stopa, Bożena; Piejko, Karolina; Ostaszewski, Krzysztof; Dziura, Robert; Galus, Łukasz; Ziółkowska, Barbara; Kempa-Kamińska, Natasza; Ziętek, Marcin; Bal, Wiesław; Kamycka, Agnieszka; Dudzisz-Śledź, Monika; Kubiatowski, Tomasz; et al.
Abstract : Pembrolizumab and nivolumab (anty-PD-1 antibody) are commonly used for the treatment of melanoma patients. However, their efficacy and safety have never been directly compared, leaving little guidance for clinicians to select the best therapy. The study included patients with inoperable or metastatic melanoma treated in first line with anti-PD-1 immunotherapy (nivolumab or pembrolizumab). In total 1037 patients were enrolled in the study, 455 (44%) patients were treated with pembrolizumab and 582 (56%) with nivolumab. The estimated median overall survival (OS) in the pembrolizumab and nivolumab groups was 17.4 and 20.0 months [ P = 0.2323; hazard ratio (HR), 1.1; 95% confidence interval (CI), 0.94–1.28], respectively, whereas the median progression-free survival (PFS) was 5.6 and 7.5 months ( P = 0.0941; HR, 1.13; 95% CI, 0.98–1.29), respectively. The estimated 2- and 3-year OS in the pembrolizumab and nivolumab groups were 42/34% and 47/37%, respectively, and the PFS was 25/21% and 29/23%, respectively. There were 391 (49%) immune-related adverse events (irAEs) of any grade during treatment, including 133 (42%) related to pembrolizumab treatment and 258 (53%) to nivolumab treatment. A total of 72 (9.6%) irAEs were in G3 or G4, including during pembrolizumab 29 (9%) and nivolumab 48 (11%). There were no differences in OS, PFS and overall response rates between nivolumab and pembrolizumab therapy in previously untreated patients with advanced/metastatic melanoma. There were no differences in the frequency of G1/G2 or G3/G4 irAEs. The choice of treatment should be based on the preferences of the patient and the clinician.